Beta endorphin selectively stimulates aldosterone secretion in hypophysectomized, nephrectomized dogs. - Güllner, H G (1983)
We examined the effects of synthetic human beta-endorphin (beta END) and a stable methionine (Met)-enkephalin analogue on aldosterone and cortisol secretion rates in anesthetized, hypophysectomized, and nephrectomized dogs and compared them to those of (1-39) ACTH. The circulation of the adrenal glands was completely isolated on the arterial and venous sides (Hilton Pouch). The peptides were infused to deliver 3 pmol/min into the aortic "pouch." Blood was collected from the vena caval pouch, which received blood only from the adrenal gland. Secretion rates of aldosterone and cortisol were calculated as the product of adrenal blood flow and venous steroid concentration. Duplicate steroid measurements were obtained during a control period, at 10, 30, and 50 min of peptide infusion and during a postcontrol period. BetaEND increased aldosterone secretion rate from 2.4 +/- 0.5 ng/min (mean +/- SEM) to 3.2 +/- 0.9 ng/ min at 10 min (N.S.), 8.2 +/- 2.5 ng/min (P less than 0.05) at 30 min and 11.0 +/- 3.7 ng/ min (P less than 0.05) at 50 min of infusion. Cortisol secretion rate was not affected by infusion of betaEND. Infusion of the stable Met-enkephalin analogue D-alanine2; Metphenylalanine4, Met(O)-enkephalin-ol or saline alone had no effect on aldosterone or cortisol secretion rates. ACTH infusion increased mean aldosterone secretion rate by approximately 215% and significantly stimulated cortisol secretion rate. These results indicate that beta END selectively stimulates aldosterone secretion with a potency similar to that of an equimolar dose of ACTH.